Women Pirates Learning Through Legitimate Peripheral Participation: Applying Theory to Shape a Fictional Narrative Based on Historical Fact - Taber, Nancy (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2023)
In this field note article, I discuss my in-progress historical novel about privateering in the 17th century to demonstrate how adult education feminist theories of situated learning have influenced my fiction-based research. I introduce situated learning in gendered communities of practice, explain women’s experiences in (para)military organizations, and describe fiction-based research. I then compare theoretical concepts and quotations with excerpts from my fiction to explore feminist situated learning adult education theories, women in non-traditional roles, fiction-based research, and how women’s lives from the 17th century connect to those in the 21st. I conclude with a discussion of how adult educators can use fiction to engage with theory in their own teaching and research. In ways similar to Watson (2016), who argues that “fiction offers sociologists a medium for doing sociological work” (p. 434), in this article, I explore how fiction can offer adult educators a medium for doing pedagogical work.